2000
DOI: 10.1007/s005350070079
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic enteritis observed during alpha-interferon therapy for chronic hepatitis C

Abstract: We report a patient with chronic hepatitis C who developed eosinophilic enteritis while being treated with recombinant interferon alpha-2b. He had no history of either allergic disorders or recurring episodes of abdominal cramps, nausea, or diarrhea. He also had had a normal eosinophil count prior to the interferon treatment. After a 12-week course of interferon alpha-2b, he began to complain of severe abdominal pain, diarrhea, and abdominal fullness. His peripheral eosinophil count increased to 45% (absolute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Two patients with CT scans describing peritoneal involvement [18,56] and another one with gastrointestinal wall thickening [37], underwent surgery and peritoneal fragments from all 3 subjects were sent for histological analysis. In 10 out of 19 cases with endoscopic lesions (1) [34], peritoneal involvement (1) [15], gastrointestinal wall thickening (3) [49,[57][58], endoscopic lesions with gastrointestinal wall thickening (1) [59], as well as in peritoneal involvement and gastrointestinal wall thickening association (1) [ [63][64]. Associations between EGE and autoimmune diseases were described in 3 patients: one with systemic lupus erythematosus [65], one with lupusscleroderma overlap syndrome and heterozygous bthalassemia [57], and another one presenting positive antinuclear antibodies [50].…”
Section: Eosinophilic Gastroenteritis (Ege)mentioning
confidence: 99%
“…Two patients with CT scans describing peritoneal involvement [18,56] and another one with gastrointestinal wall thickening [37], underwent surgery and peritoneal fragments from all 3 subjects were sent for histological analysis. In 10 out of 19 cases with endoscopic lesions (1) [34], peritoneal involvement (1) [15], gastrointestinal wall thickening (3) [49,[57][58], endoscopic lesions with gastrointestinal wall thickening (1) [59], as well as in peritoneal involvement and gastrointestinal wall thickening association (1) [ [63][64]. Associations between EGE and autoimmune diseases were described in 3 patients: one with systemic lupus erythematosus [65], one with lupusscleroderma overlap syndrome and heterozygous bthalassemia [57], and another one presenting positive antinuclear antibodies [50].…”
Section: Eosinophilic Gastroenteritis (Ege)mentioning
confidence: 99%
“…Some of these medications include carbamazepine [96], gold compounds [97], rifampicin [98], naproxen and other non-steroidal anti-inflammatory drugs [99,100], interferon [101], azathioprine [102], gemfibrozil [103], clofazimine [104], and enalapril [105]. Saeed et al reported three cases of EC in liver transplant recipients, maintained on tacrolimus [106].…”
Section: Differential Diagnosismentioning
confidence: 99%
“…It may be of significance that our patient received interferon α treatment because of recurrent post-transplant hepatitis C before the development of symptoms, later attributed to eosinophilic enteritis. Notably, eosinophilic enteritis has been already reported only in a single non–transplanted patient receiving interferon α therapy for hepatitis C,10 which suggests, however, that interferon induced immune stimulation may be capable of triggering an eosinophilic reaction. This matter is further complicated in liver transplant recipients by the need for maintenance immunosuppression to control cellular rejection.…”
Section: Discussionmentioning
confidence: 99%